A randomised crossover trial comparing the Airtraq ® NT, McGrath ® MAC and Macintosh laryngoscopes for nasotracheal intubation of simulated easy and difficult airways in a manikin - Gómez-Ríos,Manuel Ángel (2016)
ABSTRACT OBJECTIVE: Several devices can aid nasotracheal intubation when managing difficult airways. The McGrath MAC and Airtraq NT were compared with a Macintosh laryngoscope when studying the performance of anaesthetists with different levels of experience, in a manikin model of easy or difficult airway scenarios. METHODS: Sixty-three anaesthetists were recruited into a randomised trial in which each performed nasotracheal intubation with all laryngoscopes, in both scenarios. The main endpoint was intubation time. Additional endpoints included laryngoscopic view, intubation success, number of optimisation manoeuvres, audible dental clicks and the force applied to the upper airway. RESULTS: Intubation time was significantly shorter using the McGrath MAC in both scenarios and using the Airtraq in the difficult scenario, when compared with the Macintosh laryngoscope. Both devices gave more Cormack and Lehane grade 1 or 2 views than the Macintosh in the difficult scenario (p < 0.001). The McGrath MAC had the best first-attempt success rate (98.4% vs. 96.8% and 95.8%, p < 0.001 for the Airtraq NT and Macintosh laryngoscopes respectively). The number of optimisation manoeuvres, audible dental clicks and subjective assessment of the degree of force applied were significantly lower for indirect laryngoscopes versus the Macintosh laryngoscope (p < 0.001). CONCLUSION: In a manikin, the Airtraq and the McGrath laryngoscopes appeared superior to the Macintosh laryngoscope when dealing with simulated airway scenarios. Both devices were associated with better views, intubation times and rates of success, especially in a simulated "difficult airway". Overall satisfaction was highest with the McGrath laryngoscope. Similar clinical studies are needed.